Perancangan Enterprise Architecture Pada PT Vitapharm Menggunakan Framework TOGAF - Ignatius Adrian Mastan; Mario Stefanus (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2021)
PT Vitapharm is a leading cosmetic company in Indonesia that produces cosmeticproducts. In its operational activities, PT Vitapharm still has several obstacles in its business processes, one of the main problems is that some processes still use manual systems and have not yet integrated one process with another because there is no adequate information technology support. Thus, the business processes within the company have not been able to support the company to achieve organizational goals. Therefore, PT Vitapharm requires an Enterprise Architecture design so that the company's business goals can be achieved with the help of information technology. To solve the problems faced by PT Vitapharm can be completed by designing an Enterprise Architecture with the TOGAF framework. TOGAF framework was chosen because it can design and solve problems faced by PT Vitapharm. The stages of designing an Enterprise Architecture with the TOGAF framework start from the preliminary phase, requirements management, architecture vision, business architecture, information system architecture, technology architecture, opportunities and solutions, and migration planning. This study does not use the implementation governance and architecture change management stages. Research using the TOGAF framework produces an enterprise architecture design that can answer the needs of PT Vitapharm in order to adapt to the Information System/Information Technology strategic planning. The results of this study are designs that can be used by PT Vitapharm and become PT Vitapharm's reference in compiling business process improvements so that they can improve the company's internal business processes and can improve operational activities, and can achieve company goals.